Authigenic and Detrital Minerals in Peat Environment of Vasyugan Swamp, Western Siberia - Maxim Rudmin (Minerals, 2018)
Studies of mineral-forming processes in modern peat bogs can shed light on metal concentrations and their cycling in similar environments, especially in geological paleoanalogs. In terms of the mineralogical and geochemical evolution of peat bog environments, the Vasyugan Swamp in Western Siberia is a unique scientific object. Twelve peat samples were collected from the Vasyugan Swamp up to the depth of 275 cm at 25 cm intervals. The studied peat deposit section is represented by oligotrophic (0–100 cm), mesotrophic (100–175 cm), and eutrophic (175–275 cm) peat, and this is underlain by basal sediments (from 275 cm). About 30 minerals were detected using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy. The observed minerals are divided into detrital, clay, and authigenic phases. The detrital minerals found included quartz, feldspar, ilmenite, rutile, magnetite, zircon, and monazite. When passing from basal to oligotrophic bog sediments, the clay minerals changed from illite-smectite to kaolinite. Authigenic minerals are represented by carbonates (calcite and dolomite), iron (hydro-)oxides, galena, sphalerite, pyrite, chalcopyrite, Zn-Pb-S mineral, barite, baritocelestine, celestine, tetrahedrite, cassiterite, REE phosphate, etc. The regular distribution of mineral inclusions in peat is associated with the (bio)geochemical evolution of the environment. The formation of authigenic Zn, Pb and Sb sulfides is mainly confined to anaerobic conditions that exist in the eutrophic peat and basal sediments. The maximum amount of pyrite is associated with the interval of 225–250 cm, which is the zone of transition from basal sediments to eutrophic peat. The formation of carbonate minerals and the decreasing concentration of clay in the association with local sulfide formation (galena, sphalerite, chalcopyrite, stibnite) begins above this interval. The peak of specific carbonation appears in the 125–150 cm interval of the mesotrophic peat, which is characterized by pH 4.9–4.5 of pore water. Kaolinite is the dominant clay mineral in the oligotrophic peat. Gypsum, galena, chalcopyrite, sphalerite, and relicts of carbonate are noted in association with kaolinite. Changes in oxygen concentrations are reflected in newly formed mineral associations in corresponding intervals of the peat. This can be explained by the activity of microbiological processes such as the anaerobic oxidation of methane (AOM) and bacterial sulfate reduction (BSR), expressed in specific carbonatization (100–225 cm) and sulfidization (175–250 cm), respectively.